The prevalence of CYP2C19 mutations in Turkish patients with dyspepsia - Altay ÇELEBİ; Orhan Kocaman; Hakan SAVLI; Cem AYGÜN; Buğra Tolga KONDUK; Ömer ŞENTÜRK; Sadettin HÜLAGÜ (Turkish Journal of Gastroenterology, 2019)
-